Thiazolothiazole‐Based Quinoidal Compounds for High‐Performance n‐Channel Organic Field‐Effect Transistors with Low‐Cost Metal Electrodes - Yan Feng; Xiaolan Qiao; Guangcheng Ouyang; Guohua Liu; Hongxiang Li (Advanced Electronic Materials)
Abstract Thiazolothiazole‐based quinoidal molecules B1 and B2 are designed and synthesized. B1 and B2 have low‐lying lowest unoccupied molecular orbital energy levels of −4.47 and −4.41 eV, respectively. In thin films, B1 forms J‐type aggregation while B2 adopts H‐type aggregation. B1 and B2 can react with copper and silver metals and form charge transfer salts. Thin‐film transistor characteristics show both compounds display n‐channel field‐effect behavior, and the Ag and Cu source–drain electrode‐based devices exhibit similar mobility as Au source–drain electrode‐based ones. B1‐based transistors with Au, Cu, and Ag electrodes exhibit electron mobilities of 0.54, 0.45, and 0.39 cm2 V−1 s−1, respectively. The mobility of B2 is 0.061 cm2 V−1 s−1 for Au electrode‐based devices, 0.081 cm2 V−1 s−1 for Cu electrode‐based devices, and 0.09 cm2 V−1 s−1 for Ag electrode‐based devices. The self‐doping layer formed by the reaction of electrodes (Ag, Cu) and organic semiconductors (B1 and B2), at the interface of electrode/organic semiconductor is responsible for the high performance of Ag and Cu electrode‐based devices. All these results demonstrate the introduction of self‐doping layer at electrode/organic semiconductor is a general strategy to fabricate high performance transistors with low cost metals Ag and Cu as source–drain electrodes.